Simulation of solid fuel combustion in the cyclone combustion chamber using fluent-14.0 - Mohamad Mokhtar, Shah Jahan (2014)
Al-Qur’an is Holy Scripture of Islam therefore the printed text itself is treated with a great deal of respect. Unavoidably, there are times when an Al-Qur’an needs to be disposed and burning is one of the method but it require to make sure the scripture is fully burnt and the ashes produce is in the controlled condition. The best way to done this method is by using the Cyclone Combustion chamber. Cyclone combustor is known as the separator of the ash from the gaseous products of the solid fuel. The objectives of this study are to demonstrated the flow characteristic, identify velocity and temperature distributions inside the combustor and to attain the complete combustion process with stoichiometry amount of air is used. The parameters of the simulation were run by using multiphase model, incompressible flow, Realizable k-epsilon turbulent method and heat transfer. The simulation was done by using ANSYS FLUENT version 14.0. The papervolatiles-air used as mixture phase and air as liquid phase. The inlets velocities for fuel and air are 0.0254 m/s and 14.14 m/s. The simulation was run with prediction the combustion already occur so the chamber walls was set as the hot wall with temperature 773K. Others walls, inlets and outlets were assumed at the ambient temperature, 303K. The simulation results show that the design of inlets merge was influenced the mixture velocity, the higher swirl effect and the temperature increased gradually in the spinning and swirling manner occur can be visualized. The combustion mixture found as rich mixture, so the new air inlet diameter or velocity been suggested for archive the complete combustion. Simulation of new air inlet velocity shows that higher velocity and stagnation temperature occur much faster and the temperature distribution in the emission chimney was lower. As a result that chimney design may use other cheaper capable material.